Project x: ducks - Lane, Alex (Oxford University Press Karachi, 2009)
A children's book that focuses on the journey of ducks as they lay eggs, care for their nests, and raise their ducklings. It explores themes of family, nature, and the life cycle of ducks in an engaging and educational way. The story likely highlights the challenges and joys the ducks face, making it a delightful read for young audiences interested in wildlife and the natural world.